Homoeopathy in Management of Dysmenorrhoea (Homoeopathy for All, 2026)
Dysmenorrhoea is a common gynaecological condition faced by females of reproductive age group affecting 16% - 91% in various degrees. Unfortunately, dysmenorrhoea is mostly under diagnosed as it is mostly under reported among all other health conditions where females mostly depend on over-the-counter drugs which are known with various adverse health conditions. Homoeopathy along with proper management is known to give permanent relief from dysmenorrhoea. This literature is aimed to highlight few homoeopathic therapeutics in treating dysmenorrhoea along with various scales to assess improvement post homoeopathic intervention.
Keywords: Dysmenorrhoea; Homoeopathy; Therapeutics Abbreviations; Primary Dysmen orrhoea (PD); Prostaglandin (PG); Secondary Dysmenorrhoea (SD)